2020
DOI: 10.1097/md.0000000000019752
|View full text |Cite
|
Sign up to set email alerts
|

Egg consumption and risk of type 2 diabetes mellitus in middle and elderly Chinese population

Abstract: Data on the association between egg consumption and the risk of type 2 diabetes mellitus (T2DM) in the Chinese population are scarce. In the present study, we aimed to examine the association between egg consumption and the risk of T2DM in a middle and elderly Chinese population. A total of 3298 subjects (1645 men and 1653 women) from the Nutrition and Health Survey (2015–2017) in Hangzhou city were selected for the final analysis. Egg consumption was assessed using a validated food frequency questionnaire. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The same trend was observed in Korean T2DM patients, and higher egg consumption increased the risk for CVD, thus providing a basis for the development of an optimal dietary cholesterol intake guideline for the Korean population [109]. In middle-aged and elderly Chinese people, the association between egg consumption and T2DM was nonlinear, and higher egg consumption was not associated with an elevated risk for T2DM [101]. However, another Chinese study showed higher egg consumption is associated with an increased risk of diabetes and with the same amount of intake, women were at an increased risk than men [110].…”
Section: Egg and Type 2 Diabetes Mellitussupporting
confidence: 54%
See 1 more Smart Citation
“…The same trend was observed in Korean T2DM patients, and higher egg consumption increased the risk for CVD, thus providing a basis for the development of an optimal dietary cholesterol intake guideline for the Korean population [109]. In middle-aged and elderly Chinese people, the association between egg consumption and T2DM was nonlinear, and higher egg consumption was not associated with an elevated risk for T2DM [101]. However, another Chinese study showed higher egg consumption is associated with an increased risk of diabetes and with the same amount of intake, women were at an increased risk than men [110].…”
Section: Egg and Type 2 Diabetes Mellitussupporting
confidence: 54%
“…The relationship between egg intake and risk of T2DM is also complicated. In observation studies reported from several countries, no association is observed between egg consumption and T2DM in healthy persons or no hazardous in T2DM patients [3,4,9,[97][98][99][100][101]. In some cases, egg consumption lowers the risk of T2DM or ameliorates glycemic control [96,[102][103][104][105][106][107].…”
Section: Egg and Type 2 Diabetes Mellitusmentioning
confidence: 93%
“…In a study conducted on middle‐aged and older individuals in Korea, it was discovered that egg consumption was negatively correlated with the risk of T2DM in men, but indicated the presence of gender differences in women (Lee & Kim, 2018). Other research affirmed the relationship between egg consumption and T2DM is not linear and higher egg consumption is not associated with high risk of T2DM in middle‐aged and elderly Chinese people, however, it is indicated that future prospective studies are needed to confirm these findings (Ni et al., 2020). Additionally, a cohort study in the United Kingdom suggested that high egg intake was associated with higher blood sugar concentration and negative cardiovascular outcomes in T2DM patients (Guo et al., 2018).…”
Section: Egg Consumption and Diabetes Mellitusmentioning
confidence: 99%
“…Furthermore, as we have seen in unadjusted analyses, other authors found associations compatible with possible benefits of egg consumption on blood sugar levels. For example, in a cross-sectional study of more than 3 thousand Chinese adults, a dose–response curve showed that with the increase in egg consumption, the risk of type 2 diabetes first increased and then decreased 32 . Some authors argue that the protective effect of the eggs consumed on glycemia could be due to the higher intake of specific bioactive components of this food involved in the pathophysiology of type 2 diabetes 33 , specifically choline and polyunsaturated fatty acids (linolenic and docosahexaenoic acids) 34 .…”
Section: Discussionmentioning
confidence: 99%